A view from the outside: Reflections on Relational Systems Evaluation. Issue 169 (26th April 2021) - Bollinger, Richard
Abstract: This paper provides a review of the current volume and RSE. The author is a senior program officer at the John Templeton Foundation, which has funded some of the work described in this volume. He brings a unique perspective as he has both observed RSE in practice and experienced it first hand as a participant in strategic planning processes that use RSE. In addition, several of the grantees in his portfolio have implemented RSE as part of their projects. This paper offers reflections on these experiences as well as on the information presented in the volume and provides a critical review of RSE, including its strengths and weaknesses.